Reported Case of Asymptomatic SARS-CoV-2-carriage in the Child with Severe Chronic Disease - Irina I. Spichak; Larisa V. Moiseeva; Irina P. Karimova; Rafiia K. Babik; Galina N. Kireeva (Union of pediatricians of Russia, 2020)
.